2019
DOI: 10.1002/dev.21828
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and cortisol reactivity during a social evaluative stressor: A study of post‐institutionalized youth

Abstract: In the current study, we compared emotion regulation abilities between post-institutionalized (PI; N = 124) and never-institutionalized non-adopted (NA; N = 172) children and adolescents (7-15 years). We assessed cortisol reactivity and coded emotion regulation during the speech portion of Trier Social Stress Test (TSST-M). Parents reported on their children's social, academic, and behavioral adjustment. Results suggest that emotion regulation abilities increased with age, but this increase was greater for NA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(93 reference statements)
2
9
0
Order By: Relevance
“…Of course, psychological and extra‐hypothalamic physiological pathways are of interest in and of themselves and may suggest targets of intervention to improve stress functioning. We have chosen a few extra‐hypothalamic physiological and limbic psychological processes to focus on here based on whether there was evidence to support mediation or moderation, as well as theoretical arguments regarding their role as mediators of early life adversity (e.g., Wismer Fries et al, 2008; Humphreys et al, 2015; Johnson et al, 2018; Kuhlman et al, 2017; McLaughlin et al, 2015; Perry et al, 2019; Silverman and Sternberg, 2012; Van Hulle et al, 2012).…”
Section: Models Of Neglectmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, psychological and extra‐hypothalamic physiological pathways are of interest in and of themselves and may suggest targets of intervention to improve stress functioning. We have chosen a few extra‐hypothalamic physiological and limbic psychological processes to focus on here based on whether there was evidence to support mediation or moderation, as well as theoretical arguments regarding their role as mediators of early life adversity (e.g., Wismer Fries et al, 2008; Humphreys et al, 2015; Johnson et al, 2018; Kuhlman et al, 2017; McLaughlin et al, 2015; Perry et al, 2019; Silverman and Sternberg, 2012; Van Hulle et al, 2012).…”
Section: Models Of Neglectmentioning
confidence: 99%
“…There is also some evidence that emotion regulation modulates CORT responses (Doom and Gunnar, 2015). Specifically, those with high emotion regulation time their stress responses differently than those with less regulation, elevating in anticipation of the stressor and resulting in less of a response during the stressor and a faster recovery once the stressor is over (Perry et al, 2019; Susman et al, 1997). On the other hand, when encountering the stressor in the first place is a result of poor self‐regulation (e.g., poor regulation leads to aggression which leads to peer rejection), children with greater self‐regulatory abilities may encounter fewer stressors throughout the day (Gunnar et al, 2003).…”
Section: Models Of Neglectmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the neurobiological research on aggressive behavior has focused on the two primary arms of the human stress response system: the HPA axis and the autonomic nervous system (ANS), with the latter comprising sympathetic (SNS) and parasympathetic (PNS) subsystems. The HPA axis is a slow-acting system that is contingent on the perception of threat, particularly threats that are social and evaluative in nature (Dickerson & Kemeny, 2004; Johnson, Perry, Hostinar, & Gunnar, 2019; Perry, Donzella, Parenteau, Desjardins, & Gunnar, 2019). Stress-specific activation of the HPA axis is initiated via appraisals of threat signaling the paraventricular nucleus of the hypothalamus to instigate a cascade of releasing hormones terminating in the adrenal cortex with the secretion of cortisol (Ulrich-Lai & Herman, 2009).…”
Section: Biological Underpinnings Of Behaviormentioning
confidence: 99%
“…For example, the SNS and HPA share structural underpinnings in the amygdala; however, the central nucleus is preferentially involved in sympathetic reactivity, whereas the medial and basal amygdala nuclei appear to be more directly activated as part of the HPA response (Ulrich-Lai & Herman, 2009). Although it has been suggested that the HPA axis is activated specifically by social-evaluative threat whereas the SNS can be activated by nonsocial stimuli (Gruenewald, Kemeny, Aziz, & Fahey, 2004; Johnson et al, 2019; Perry et al, 2019; Schommer, Hellhammer, & Kirschbaum, 2003), there is evidence that social contexts are predictive of the magnitude of overall stress responsivity but not the pattern of physiological activation across multiple systems (Bosch et al, 2009).…”
Section: Psychophysiology Of Aggressionmentioning
confidence: 99%